Conflict, commerce, and an aesthetic of appropriation in the Italian maritime cities, 1000-1150 - Mathews, Karen R.
1 online resource (238 pages)
Keywords: In Conflict, Commerce, and an Aesthetic of Appropriation in the Italian Maritime Cities, 1000-1150 , Karen Rose Mathews analyzes the relationship between war, trade, and the use of spolia (appropriated objects from past and foreign cultures) as architectural decoration in the public monuments of the Italian maritime republics in the eleventh and twelfth centuries. This comparative study addressing five urban centers argues that the multivalence of spolia and their openness to new interpretations made them the ideal visual form to define a distinct Mediterranean identity for the inhabitants of these cities, celebrating the wealth and prestige that resulted from the paired endeavors of war and commerce while referencing the cultures across the sea that inspired the greatest hostility, fear, or admiration.